Perbandingan Efektifitas Antara Minyak Atsiri Kulit Batang Kayu Manis (Cinnamomum burmannii) dengan Temephos sebagai Larvasida Aedes aegypti - Al Kamal, Muhamad Rizki; Syafei, Neneng Syarifah; Nasution, Gita Tiara Dewi (UI Scholars Hub, 2017)
Dengue fever is a major health issue in the world. Preventive measure with temephos/abate has long been used to combat this problem. Istiana et al reported that there were cases of resistance of Aedes aegypti larvae to temephos in various parts of the world, including Indonesia. Indonesian Cinnamon (Cinnamomum burmannii) has been proven to possess larvacide effect and can be used as an alternative insecticide. This research was meant to compare the larvacide effect of Indonesian cinnamon (Cinnamomum burmannii) essential oil to the larvacide effect of temephos against Aedes aegypti larvae. This research used laboratory experimental design analysis. The total number of samples were 20 larvae of Aedes aegypti at 3rd and 4th instar which were tested four times on each four experimental groups. The collected data were the total number of Aedes aegypti larva deaths observed 24 hours after the variables were applied. The analysis of the results was done by using statistic analysis program. There were significant differences on larva deaths due to the essential oil and abate variables with p value < 0.001. The results were as follows: negative control death (0%), emulsifier (2.5%), essential oil (22.5%), and abate (100%). The larvacide effectiveness of abate is significantly better than that of Indonesian cinnamon essential oil.